MODEL MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS MASYARAKAT DALAM RANGKA PENGEMBANGAN MADRASAH BERMUTU DI MTs AL HIKMATURROHMANIYAH SUKOREJO PASURUAN - Suadi (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: The article discusses the financing management model at MTs AlHikmaturrohmaniyah Sukorejo Pasuruan. A qualitative approach with descriptive analysis was used in this study. The technique of collecting data is by interview, observation, and documentation. The author uses the Miles and Hubberman models, data reduction, data display, and verification / conclusion in analyzing data. The results of the study show: first, the financing management model at MTs Al-Hikmaturrohmaniyah Sukorejo Pasuruan has been systematically following the management process, namely by implementing three important paths in which includes planning income and expenditure budgets, overseeing education financing that departs from the planned needs of both madrasah and the provisions of the local ministry of religion, the use of education funding is with certain considerations and priorities in previous planning, and supervision of education funding as a control and evaluation for future improvements. Second, the application of the financing management model at MTs Al Hikmarurrohmaniyah Sukorejo Pasuruan is in accordance with the principles of quality development in the financing sector with procedures for planning, budgeting, supervision, and reporting. This is in accordance with the concept of quality management that the development of quality is all forms of development activities that must go through the process of planning, implementation, and reporting. Keywords: Financing Management, Quality, Budget